Oleuropein-Enriched Extract From Olive Mill Leaves by Homogenizer-Assisted Extraction and Its Antioxidant and Antiglycating Activities - Márquez, Katherine; Márquez, Nicole; Ávila, Felipe; Cruz, Nadia; Burgos-Edwards, Alberto; Pardo, Ximena; Carrasco, Basilio (Frontiers in Nutrition, 2022)
Olive oil consumption has increased in the last two decades and consequently, its wastes have increased, which generates a tremendous environmental impact. Among by-products, are the olive mill leaves, which are easier and inexpensive to treat than other olive by-products. However, little research has been done on their chemical composition and potential bioactivity. Hence, in this study, olive mill leaves were used to obtain Oleuropein-Enriched Extracts (OLEU-EE) using Conventional Extraction, Ultrasound-Assisted Extraction, and Homogenization-Assisted Extraction. These three techniques were evaluated using a Factorial Design to determine the parameters to obtain an OLEU-EE with high content of Total Phenolic Compounds (TPC), Antioxidant Activity (AA), and Oleuropein concentration (OLEU). From the results, Homogenizer-Assisted Extraction (HAE) technique was selected at 18,000 rpm, solid: liquid ratio 1:10, and 30 seconds of homogenization with 70% ethanol, due to its high TPC (5,196 mg GA/100 g), AA (57,867 µmol of TE/100 g), and OLEU (4,345 mg of OLEU/100 g). In addition, antiglycating effect of OLEU-EE on the levels of 1) fluorescent Advanced Glycation End Products (AGEs) were IC50 of 0.1899 and 0.1697 mg/mL for 1λEXC 325/λEM 440; 2λEXC 389/λEM 443, respectively; 2) protein oxidative damage markers such as dityrosine (DiTyr), N-formylkynurenine (N-Formyl Kyn), and kynurenine (Kyn) were IC50 of 0.1852, 0.2044 and 0.1720 mg/mL, respectively. In conclusion, OLEU-EE from olive mill leaves has different capacities to inhibit AGEs evidenced by the IC50 of fluorescent AGEs and protein oxidation products, together with the scavenging free radical evidenced by the concentration of Trolox Equivalent. Therefore, OLEU-EE could be potential functional ingredients that prevent oxidative damage caused by free radicals and AGEs accumulation.